Optimalisasi Literasi Digital Keuangan pada Usaha Mikro, Kecil dan Menengah untuk Mendukung Transparansi dan Efisiensi Ekonomi Berkelanjutan - Nasution, Emmi Suryani; Syamsidar, Syamsidar (Forum Kerjasama Pendidikan Tinggi, 2026)
This community service activity aims to improve the financial digital literacy of MSME actors in Lampupok Village, Aceh Besar, as an effort to promote transparency and efficiency in village financial management. The main problem faced by MSMEs is their limited ability to use digital technology for financial recording and reporting, which affects business accountability and efficiency. The implemented solutions include an initial survey to identify the level of digital literacy, training on the use of digital bookkeeping applications, implementation assistance, and post-training monitoring and evaluation. The results show an increase in financial digital literacy scores from 45 to 75, a rise in MSMEs regularly preparing digital financial reports from 25% to 80%, and a reduction in manual recording time from an average of 5 hours to 2 hours per week. Furthermore, 90% of participants expressed satisfaction or high satisfaction with the program. This activity demonstrates that improving financial digital literacy can enhance the performance, transparency, and credibility of MSMEs before financial institutions. However, limited internet access and technical skills remain challenges to be addressed in future programs.